Analysis of Cascaded H-Bridge Multilevel Inverter with Distributed MPPT for Grid-Connected PV Applications (International Journal of Engineering and Computer Science, 2017)
A modular cascaded H-bridge multilevel inverter for single- or three-phase grid-connected PV applications has been presented in this paper. The modular cascaded multilevel topology helps to improve the efficiency and flexibility of PV systems. To realize better utilization of PV modules and maximize the solar energy extraction, a distributed maximum power point tracking control scheme is applied to both single-phase and three-phase multilevel inverters, which allows independent control of each dc-link voltage. For three-phase grid-connected PV applications, PV mismatches may introduce unbalanced supplied power, leading to unbalanced grid current. To solve this problem, a control scheme with modulation compensation is also proposed. The simulated three-phase seven-level cascaded H-bridge inverter has been built utilizing nine Hbridge modules (three modules per phase). Each H-bridge module is connected to a 185 W PV panel. Simulation results are presented to verify the feasibility of the proposed approach.